The heterogeneity of Kosovel’s, Mrak’s and Delak’s dramatic experiments - Toporišič, Tomaž (Slavia Centralis, 2023)
The essay deals with the attempts of Srečko Kosovel, Ferdo Delak and Ivan Mrak to form a contemporary, modernist or avant-garde drama. This diversity of their writings can be partly explained by anomalies in the distribution and reception of their concepts, performances and texts, but at the same time (as Marko Juvan did with Kosovel) they can be understood “as an eminent symptom of modernism as a system of divergent sociolects responding to a common problematic complex.” All three avant-gardists, however, certainly understood new forms and new avant-garde art as follows: “The modern poet breaks down form to come to vivid direct life” (Kosovel). With the dramatic hybrids of Kosovel, Mrak and Delak, the art in Slovenia asserted the particular kinds of tensions between the grotesque and the sublime, the poetic and the almost documentary, which were characteristic Futurist, Constructivist and Expressionist aesthetics of the time.
Keywords: Historical Avant-Gardes; New Drama; Hybrid Modernism; Hymnic Tragedy; Constructivism; Expressionism; Futurism